PENGUATAN KOMPETENSI GURU PENDIDIKAN JASMANI DI KECAMATAN LEIHITU KABUPATEN MALUKU TENGAH - Jonas Solissa; Emma Rumahlewang; Bahmid Hasbullah (Universitas Pattimura, 2023)
The performance of Physical Education Sports and Health teachers in the learning process in Leihitu District, Central Maluku Regency is still not optimal. This service activity aims to determine the level of competence of Physical Education, Sports and Health Teachers in Leihitu District, Central Maluku Regency in 2022. The training methods in this community service activity are lectures, discussions and questions and answers. The instrument used to measure the level of teacher competency is the Teacher Performance Assessment Instrument. The subjects in this service were Physical Education, Sports and Health Teachers in Leihitu District, Central Maluk Regency, totaling 40 teachers from 21 schools. Data analysis techniques use descriptive analysis as outlined in the form of percentages. The results of the evaluation of the training materials show that the competency level of Physical Education, Sports and Health Teachers in Leihitu District, Central Maluku Regency is in the